2007
DOI: 10.4049/jimmunol.178.10.6495
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Apoptosis and High-Mobility Group Protein 1 Release from Murine Macrophages Stimulated with Lipopolysaccharide or Polyinosinic-Polycytidylic Acid

Abstract: High-mobility group protein 1 (HMGB1) is a nonhistone nuclear protein whose function depends on cellular location. Inside the cell, HMGB1 modulates a variety of important cellular processes, including transcription, whereas outside the cell, HMGB1 acts as a cytokine that can promote inflammation and mediate sepsis and arthritis in animal models. In in vitro studies, proinflammatory molecules such as LPS, lipoteichoic acid, polyinosinic-polycytidylic acid (poly(I:C)), TNF-α, and type I and II IFNs can induce HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 43 publications
11
94
3
Order By: Relevance
“…Together, these results indicate that inhibiting the release of HMGB1 with Gly results in less tissue damage and better functional recovery of neurons. In accordance with our experimental results, the relationship between apoptosis and HMGB1 release in macrophages and other cells was investigated in an in vitro study, and those results indicated that the release of HMGB1 from macrophages correlated with the occurrence of apoptosis, and suggested that these processes reflected common mechanisms and could occur concomitantly [31] . However, other studies have shown that HMGB1 production occurred downstream of apoptosis in the final common pathway to organ damage in severe sepsis [32] .…”
Section: Discussionsupporting
confidence: 53%
“…Together, these results indicate that inhibiting the release of HMGB1 with Gly results in less tissue damage and better functional recovery of neurons. In accordance with our experimental results, the relationship between apoptosis and HMGB1 release in macrophages and other cells was investigated in an in vitro study, and those results indicated that the release of HMGB1 from macrophages correlated with the occurrence of apoptosis, and suggested that these processes reflected common mechanisms and could occur concomitantly [31] . However, other studies have shown that HMGB1 production occurred downstream of apoptosis in the final common pathway to organ damage in severe sepsis [32] .…”
Section: Discussionsupporting
confidence: 53%
“…The present findings that CAP11 suppressed the LPSinduced HMGB1 release and necrotic cell death but not apoptotic cell death, apparently suggest that HMGB1 is mostly released from LPS-stimulated necrotic RAW264.7 cells. In contrast, Jiang et al argued that HMGB1 is released from apoptotic RAW264.7 cells (assessed by caspase 3 activation), when stimulated with LPS or polyinosinicpolycytidylic acid (18). However, in their experiments LDH (a necrotic marker) was also extracellularly released under the stimulation conditions, and the release was correlated with HMGB1 release.…”
Section: Discussionmentioning
confidence: 71%
“…Previously, we revealed that CAP11 (cationic antibacterial polypeptide of 11-kDa), a member of cathelicidins isolated from guinea pig neutrophils, has potentials to not only kill bacteria but also neutralize LPS; CAP11 can inhibit the binding of LPS to CD14-positive target cells and protect mice from endotoxin shock (15,16). Moreover, we have found that administration of CAP11 suppresses the increase of serum HMGB1 level in mouse endotoxin shock model (17), and HMGB1 is reported to be released from macrophages by LPS-stimulation, accompanied with cell death (18). Thus, we hypothesized that CAP11 may suppress the release of HMGB1 from mononuclear phagocytes by regulating cell death of target cells in endotoxin shock model.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations